Numerical investigation of channel geometry on the performance of a PEM fuel cell - Khazaee, Iman; Mohammadiun, Mohammad (Zielona Góra: Uniwersytet Zielonogórski)
A complete three-dimensional and single phase model for proton exchange membrane (PEM) fuel cells was used to investigate the effect of using different channels geometry on the performances, current density and gas concentration. The proposed model was a full cell model, which includes all the parts of the PEM fuel cell, flow channels, gas diffusion electrodes, catalyst layers and the membrane. Coupled transport and electrochemical kinetics equations were solved in a single domain; therefore no interfacial boundary condition was required at the internal boundaries between cell components.
Keywords: PEM fuel cell; rectangular; triangular; elliptical; numerical modeling; performance